Tindak Tutur Ilokusi dalam Video Iklan yang Terdapat pada Akun Air Mineral di Media Sosial YouTube - Aimar Akbar; Idawati Idawati; Sakinah Fitri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to describe the types and functions of illocutional speech contained in mineral water accounts on YouTube social media. This study uses a qualitative method with a descriptive qualitative research design. The data source in this study came from eight advertisements consisting of four mineral water brands on YouTube social media. The data analysis used is a pragmatic approach that is carried out in detail, starting from data identification, data classification, analyzing and interpreting data, and concluding. The data from the research was obtained by grouping illocutional speech actions in the form of words, phrases, and sentences contained in mineral water advertisements. The results of the study revealed that there are five types of illocution speech acts, namely assertive, directive, commissive, expressive, and declarative. The functions found consist of the actions of reporting, affirming, predicting, claiming, acknowledging, complaining, statements, asking, commanding, suggesting, persuasive requests, offers, promises, astonishment speeches, greetings of hospitality, and announcements. These findings show that speech in advertising plays an important role in building persuasiveness and brand image on social media.